WEATHERING THE STORM: SHARIAH COMPLIANCE, DIGITAL INNOVATION, AND STOCK PERFORMANCE DURING COVID-19 - Modjo, Mohamad Ikhsan; Putridamni, Florencia; Lin, Ariella Shenny (Journal of Islamic Monetary Economics and Finance, 2025)
The COVID-19 pandemic disrupted global financial markets, highlighting the need for factors that enhance resilience. This study examines whether Shariah compliance and digital innovation, individually and together, mitigate declines in stock performance during economic downturns. Drawing on Signaling Theory and Dynamic Capabilities Theory (DCT), this study argues that Shariah compliance serves as a signal of strong governance, while digital innovation enhances adaptability. Using firm-level data from Indonesia and a difference-in-differences (DID) model, our findings suggest that both factors help firms withstand crises, with digital innovation amplifying the benefits of Shariah compliance. This study provides insights into how Islamic finance and digital transformation contribute to financial stability. ACKNOWLEDGMENT This research is funded by HIBAH Penelitian International BINUS University 2024 (BINUS International Research Grant 2024). The authors would like to express their sincere gratitude to BINUS University for the support and funding provided.